Edukasi Karakter Berbasis Teknologi Menjadi Siswa Kreatif, Beretika, dan Produktif di Era Digital” - Zurwanty, Recy Harviani; Rahmawati, Elmi; Indra, Novalia (LPPM Universitas Dharma Andalas, 2025)
The rise of digital technology is characterized by the speed and ability to access information for the business world and society (Shepherd, 2011). The digital era can be seen as a rapidly developing system where people's knowledge not only grows, but also becomes more complex, making it difficult to change their lives. Social capital is abundant in the digital age and will only increase as the technological capabilities of our knowledge base expand. The rapid development of science, technology and knowledge in the world today demands the use of humans everywhere. These changes have implications for the education sector which needs to be improved at the local, national and international levels. Character education is very important in preparing students to face the world of work and politics. It cannot be denied that technology has changed the field of education dramatically. Currently there are many concerns about the challenges of learning in the digital era, from cyberbullying to identity theft.